2011
DOI: 10.1016/j.jnoncrysol.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural relaxation of Ti40Zr25Ni8Cu9Be18 bulk metallic glass

Abstract: The enthalpy relaxation behavior of Ti 40 Zr 25 Ni 8 Cu 9 Be 18 bulk metallic glass follows the general characteristics of that for amorphous materials although its unique quenched-in nuclei/amorphous matrix structure: the annealing time dependence of recovery enthalpy follows a stretched exponential function with the mean relaxation time obeying an Arrhenius law, which may be due to the longer incubation time for crystallization τ inc than the relaxation time τ leading to the enthalpy relaxation Two parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
4
3
0
Order By: Relevance
“…Similar to the delay time confirmation of Al 88 Y 7 Fe 5 MG, for three Cu-doped Al-Y-Fe MG systems, a series of Flash DSC tests at one temperature with different annealing times were conducted. In Figure 6B, the Flash DSC heating curves are signals shift to the high temperature range, which is consistent with the previous research (Slipenyuk and Eckert, 2004;Mei et al, 2011). According to the heat flow curves in Figure 6B, the corresponding plot of T g with t a at 245°C for Al 87 Y 7 Fe 5 Cu 1 MG can be obtained as displayed in Figure 6C.…”
Section: Cu-doping Effect On Nanocrystallization Reaction and Glass Formation Ability Of Al 88 Y 7 Fe 5 Mg Systemsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the delay time confirmation of Al 88 Y 7 Fe 5 MG, for three Cu-doped Al-Y-Fe MG systems, a series of Flash DSC tests at one temperature with different annealing times were conducted. In Figure 6B, the Flash DSC heating curves are signals shift to the high temperature range, which is consistent with the previous research (Slipenyuk and Eckert, 2004;Mei et al, 2011). According to the heat flow curves in Figure 6B, the corresponding plot of T g with t a at 245°C for Al 87 Y 7 Fe 5 Cu 1 MG can be obtained as displayed in Figure 6C.…”
Section: Cu-doping Effect On Nanocrystallization Reaction and Glass Formation Ability Of Al 88 Y 7 Fe 5 Mg Systemsupporting
confidence: 88%
“…It is obvious that all of Flash DSC heat flow curves display the obvious endothermic reaction signals corresponding to glass transition and the glass transition temperature T g shifts to the higher temperature with the increase of annelaing time t anneal . These results are very close to the previous reseach on the structural relaxation effect on MGs (Slipenyuk and Eckert, 2004;Mei et al, 2011). To study the evolution of the glass transition temperature T g with annealing time t anneal , T g is plotted against t anneal at 240°C, as is shown in the middle part of Figure 3C.…”
Section: Determination Of Nucleation Delay Time In Marginal Al-based Mgssupporting
confidence: 87%
“…It is obvious that all of Flash DSC heat flow curves display the obvious endothermic reaction signals corresponding to glass transition and the Tg shifts to the higher temperature with the increase of annealing time ta. These results are very close to the previous research on the structural relaxation effect on MGs [24,25]. To study the evolution of the glass transition temperature Tg with annealing time ta, Tg is plotted against ta at 150 °C, as shown in the Figure 3b.…”
Section: Delay Time Determination In Various Amorphous Materialssupporting
confidence: 88%
“…It should be noted that the power dissipation map just helps us to locate a beneficial domain (temperature and strain rate) for optimum hot workability of BMGs; however, during the industrial manufacture, deformation time must be taken into account. For Ti 41.5 Cu 37.5 Ni 7.5 Zr 2.5 Hf 5 Sn 5 Si 1 BMG, the deformation time must be within the upper limit to avoid crystallization, since our previous investigations have shown that partial crystallization of this alloy will lead to a drastic degradation of room-temperature mechanical properties [50]. In addition, the acceleration of crystallization when the sample is deformed in the non-Newtonian flow regime will lead to shorten the upper limit of the incubation time for nucleation, as will be presented later and also should be considered during the determination of processing conditions.…”
Section: Evaluation Of Formability and Optimization Of Processing Conmentioning
confidence: 99%